A high precision apparatus for intracellular thermal response at single-cell level. (4th September 2015) - Tian, Wenjuan; Wang, Cangling; Wang, Jianqing; Chen, Qiuhua; Sun, Jianfei; Li, Can; Wang, Xing; Gu, Ning
Abstract In this work, a nanoprobe that is highly thermo-sensitive to tiny temperature changes was prepared based on a thermocouple metal junction. A series of electro-element apparatuses were integrated to accomplish single-cell temperature measurement. The temperature measurement probe (TMP) was constructed by tungsten (W), polyurethane (PU), and platinum (Pt). The tip size of TMP was characterized at less than 500 nm, and the tip angle was between 10 and 20° with the resistance in the range of 500 to 1500 Ω. The single-cell temperature measurement probes were calibrated and calculated with a Seebeck coefficient ranging from 6 to 8 μV °C−1 at a precision of 0.1 °C. Monitoring the temperature at a single-cell level by inserting the TMP in marine lung epithelia (MLE)-12 cells displayed that the stimulation of lipopolysaccharide (LPS) and cobalt chloride induced different single-cell temperature fluctuation. This investigation could help reveal complex cellular functions and develop novel diagnoses.